A detailed study of AlN and GaN grown on silicon‐on‐porous silicon substrate. Issue 4 (2nd November 2016) - Gommé, Guillaume; Gautier, Gael; Portail, Marc; Frayssinet, Eric; Alquier, Daniel; Cordier, Yvon; Semond, Fabrice
Abstract : In this study, we investigate the growth of AlN and GaN epilayers on silicon‐on‐porous silicon (SOP) as a compliant substrate. The porous silicon layers is obtained by electrochemical etching of silicon wafers in HF based solutions. Different porosities (10–30%) and porous layer thicknesses (3–30 μm) have been investigated. In order to obtain a single orientation GaN, a Si cap layer is grown on porous silicon by chemical vapour deposition leading to a smooth epi‐ready surface. Then, the subsequent growth of AlN by molecular beam epitaxy and GaN by metal‐organic chemical vapour deposition is investigated by atomic force microscopy and X‐ray diffraction. The epilayers grown on SOP show similar surface morphology and structural quality to state of the art GaN layers grown on bare silicon. In addition, strain in the GaN layers grown on SOP and Si has been investigated. Interestingly, the results indicate that a slight compliant effect is achieved on SOP substrate with the thicker porous layer.